2015
DOI: 10.1007/s10072-015-2219-9
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported Chiari malformation type I symptoms and diagnostic experiences: a report from the national Conquer Chiari Patient Registry database

Abstract: Chiari malformation (CM) is a condition in which cerebellar tonsillar ectopia may manifest with various clinical presentations. This study reports from the only national, online patient registry available, the symptoms, comorbid neurocognitive and psychological conditions, and diagnostic experiences of patients living with CM type I (CM I). The current research is one component of a large investigation designed to collect information from individuals with CM through the online Conquer Chiari Patient Registry q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
56
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 31 publications
3
56
0
5
Order By: Relevance
“…This condition of dogs has similarities to Chiari‐type 1 malformation in humans, characterized by caudal herniation of the cerebellar tonsils below the foramen magnum and also frequently associated with SM . Clinical presentation in humans is variable but manifestations of neuropathic pain dominate including headaches, neck pain, and burning sensations of the upper extremities …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This condition of dogs has similarities to Chiari‐type 1 malformation in humans, characterized by caudal herniation of the cerebellar tonsils below the foramen magnum and also frequently associated with SM . Clinical presentation in humans is variable but manifestations of neuropathic pain dominate including headaches, neck pain, and burning sensations of the upper extremities …”
mentioning
confidence: 99%
“…9 Clinical presentation in humans is variable but manifestations of neuropathic pain dominate including headaches, neck pain, and burning sensations of the upper extremities. 10 Characterizing the signs of CMSM in dogs is challenging because of the difficulty of inferring signs of pain from behavior in dogs. Owners report that affected dogs cry out in pain; exhibit phantom scratching of the neck, flank, and ear (importantly, the paw does not make contact with the skin), rub their face, neck, or ear; and show other more insidious signs such as reluctance to play, jump, or lower their head to eat.…”
mentioning
confidence: 99%
“…Additionally, rates of autism spectrum disorders (3.5%) and bipolar disorders (2.3%) in our pediatric sample were greater than national prevalence rates that approach 1% for both disorders [22]. The recent Conquer Chiari online survey of adults with CM1 [11] revealed that about one-third of adults with CM1 reported suffering from depression, and 20% endorsed clinical anxiety. While our findings are based on family report and record review, these rates are consistent with the study by Bakim et al [10], who documented a 44% rate of psychiatric disorders in an adult CM1 sample using a standardized clinical interview format.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Bakim et al [10] documented a high incidence of psychiatric disorders in a small sample of postsurgical adults with CM1. Also, a recent online survey targeting adults with CM1 revealed a high rate of self-reported mood disorders [11]. Additionally, published case reports have documented anxiety disorders [12][13][14] and psychosis associated with CM1 [15].…”
Section: Introductionmentioning
confidence: 99%
“…Chiari‐type 1 malformation in humans also is commonly associated with the development of SM, with an estimated 65%‐80% of patients developing both conditions 12, 13. People with CM1 describe a wide range of signs including numbness, neck pain, headaches, memory loss, aphasia, and even depression 14. Pain and sensory deficits in human CM1 patients have been quantified using thermal and mechanical sensory testing, and patient drawn pain maps 14, 15, 16, 17.…”
Section: Introductionmentioning
confidence: 99%